Population Health Implications of Medical Tourism. Issue 1 (July 2017) - Adabi, Kian; Stern, Carrie S.; Weichman, Katie E.; Garfein, Evan S.; Pothula, Aravind; Draper, Lawrence; Tepper, Oren M.
Abstract : Background: Fifteen million U.S. patients each year seek medical care abroad; however, there are no data on outcomes and follow-up of these procedures. This study aims to identify, evaluate, and survey patients presenting with complications from aesthetic procedures abroad and estimate their cost to the U.S. health care system. Methods: A single-center retrospective review was conducted. A cohort of patients presenting with complications from aesthetic procedures performed abroad was generated. Demographic, complication, and cost data were compiled. Patients were surveyed to assess their overall experience. Results: Over a 36-month period, 42 patients met inclusion criteria (one man and 41 women), with an average age of 35 ± 11.4 years (range, 20 to 60 years). Comorbidities included four active smokers, two patients with hypertension, and one patient with diabetes. Average body mass index was 29 ± 4.4 kg/m 2 (range, 22 to 38 kg/m 2 ). Procedures performed abroad included abdominoplasty ( n = 28), liposuction ( n = 20), buttock augmentation ( n = 10), and breast augmentation ( n = 7), with several patients undergoing combined procedures. Eleven patients presented with abscesses and eight presented with wound dehiscence. Eight of the 18 patients who were surveyed were not pleased with their results and 11 would not go abroad again for subsequent procedures. Average cost of treating the complications was $18, 211, with an estimated cost to the U.S. health care system of $1.33 billion. The main payer group was Medicaid. Conclusions: Complications from patients seeking aesthetic procedures abroad will continues to increase. Patients should be encouraged to undergo cosmetic surgery in the United States to improve patient outcomes and satisfaction and because it is economically advantageous. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.